Estrogen metabolite ratio: Is the 2-hydroxyestrone to 16α-hydroxyestrone ratio predictive for breast cancer? - Nadia Obi; Alina Vrieling; Judith Heinz (Dove Medical Press, 2011)
Nadia Obi1, Alina Vrieling2, Judith Heinz1, Jenny Chang-Claude21University Cancer Center Hamburg (UCCH)/Hubertus Wald Tumor Center, University Medical Center Hamburg-Eppendorf, Hamburg, Germany; 2Division of Cancer Epidemiology, German Cancer Research Center, Heidelberg, GermanyAbstract: Experimental studies have shown that two main estrogen metabolites hydroxylated by CYP1A1 and CYP1B1 in the breast differentially affect breast cell proliferation and carcinogenesis. Although 16α -hydroxyestrone (16α OHE1) exerts estrogenic activity through covalent estrogen receptor (ER) binding, 2-hydroxyestrone (2OHE1) presumably has antiestrogenic capabilities. The ratio of 2OHE1 to 16α OHE1 represents the relative dominance of one pathway over the other and is believed to be modifiable by diet. It was hypothesized that women with or at high risk of breast cancer have a lower estrogen metabolite ratio (EMR) compared with women without breast cancer. We conducted a systematic review on the EMR as a predictor for breast cancer. A total of nine studies (six prospective and three retrospective) matched our inclusion criteria, comprising 682 premenopausal cases (1027 controls) and 1189 postmenopausal cases (1888 controls). For the highest compared with the lowest quantile of urinary EMR, nonsignificant associations suggested at best a weak protective effect in premenopausal but not in postmenopausal breast cancer (range of odds ratios: 0.50–0.75 for premenopausal and 0.71–1.31 for postmenopausal). Circulating serum/plasma EMR was not associated with breast cancer risk. Associations were inconclusive for receptor subtypes of breast cancer. Uncontrolled factors known to be involved in breast carcinogenesis, such as 4-hydroxyestrone (4OHE1) concentration, may have confounded results for EMR. Results of the prospective studies do not support the hypothesis that EMR can be used as a predictive marker for breast cancer risk. Future research should concentrate on profiles of estrogen metabolites, including 4OHE1, to gain a more complete picture of the relative importance of single metabolites for breast cancer.Keywords: estrogen metabolite ratio, 2-hydroxyestrone, 16α -hydroxyestrone, breast cancer, predictive marker, review